Reduced humoral response to mRNA SARS‐CoV‐2 BNT162b2 vaccine in kidney transplant recipients without prior exposure to the virus. Issue 8 (7th May 2021) - Grupper, Ayelet; Rabinowich, Liane; Schwartz, Doron; Schwartz, Idit F.; Ben‐Yehoyada, Merav; Shashar, Moshe; Katchman, Eugene; Halperin, Tami; Turner, Dan; Goykhman, Yaacov; Shibolet, Oren; Levy, Sharon; et al.
Abstract : COVID‐19 is associated with increased morbidity and mortality in transplant recipients. There are no efficacy data available regarding these patients with any of the available SARS‐CoV‐2 vaccines. We analyzed the humoral response following full vaccination with the BNT162b2 (Pfizer‐BioNTech) in 136 kidney transplant recipients, and compared it to 25 controls. In order to exclude prior exposure to the virus, only participants with negative serology to SARS‐CoV‐2 nucleocapsid protein were included. All controls developed a positive response to spike protein, while only 51 of 136 transplant recipients (37.5%) had positive serology ( p  < .001). Mean IgG anti‐spike level was higher in the controls (31.05 [41.8] vs. 200.5 [65.1] AU/mL, study vs. control, respectively, p  < .001). Variables associated with null humoral response were older age (odds ratio 1.66 [95% confidence interval 1.17–2.69]), high‐dose corticosteroids in the last 12 months (1.3 [1.09–1.86]), maintenance with triple immunosuppression (1.43 [1.06–2.15]), and regimen that includes mycophenolate (1.47 [1.26–2.27]). There was a similar rate of side effects between controls and recipients, and no correlation was found between the presence of symptoms and seroconversion. Our findings suggest that most kidney transplant recipients remain at high risk for COVID‐19 despite vaccination. Further studies regarding possible measures to increase recipient's response to vaccination are required. Abstract : Most kidney transplant recipients do not mount an appreciable anti‐spike antibody response to the BNT162b2 (Pfizer‐BioNTech) SARS‐CoV‐2 vaccine.